Tradisi Maulid Pada Masyarakat Mlangi Yogyakarta - Nadia, Zunly (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
The article discusses the Maulidan tradition in Mlangi Yogyakarta. The festival as commemorating the birthday of the Prophet PBUH has become a tradition for most Muslim in Indonesia. The Maulid festival in Mlangi has descended for centuries commemorating the birthday of the Prophet PBUH. The festival shows the dialectic stance of religion and tradition seen in three related-meanings namely modernity, religion and predecessor’s cultures.